Human Resource Development Based on the Principles of Tri-sikkhā in Municipalities of San Sai District, Chiang Mai Province - Raksa-Arayawetchakul, Wisanu; Pontin, Prasert; Panyaweeratat , Noppadon (MCU Haripunchai Review, 2026)
This study aimed to 1) assess the level of human resource development (HRD) in municipalities of San Sai District, Chiang Mai Province; 2) examine the relationships between the Buddhist Threefold Training (Tri-sikkhā: sīla, samādhi, paññā) and HRD outcomes; and 3) propose Tri-sikkhā-based HRD guidelines. An explanatory sequential mixed-methods design was employed. The quantitative strand surveyed a proportionately stratified sample of 398 respondents across 12 municipalities using a structured questionnaire. Data were analyzed with descriptive statistics (frequency, percentage, mean, standard deviation) and Pearson’s correlation, with hypothesis testing at the significance level of p < 0.01. 3)The qualitative strand comprised in-depth interviews with 10 key informants from four stakeholder groups—municipal executives, municipal civil servants/employees, scholars in public administration, and Buddhist studies scholars—and was analyzed through systematic content analysis. The research findings revealed that: 1) Tri-sikkhā was at a very high level overall with wisdom (paññā) highest HRD was at a high level across all domains education development 2) The relationships between Tri-sikkhā and HRD outcomes were statistically significant overall and by dimension (p < 0.01), with effect sizes ranging from moderate to moderately high. Qualitative results explicated key mechanisms—cultivation of an ethical culture (sīla), mindful self-regulation at work (samādhi), and system/digital learning (paññā)—alongside constraints related to workload, resource limitations, and seniority-based culture. The study proposes the “KFCSMA SMART MODEL” as a structured framework for system-level, Tri-sikkhā-driven HRD in Thai municipalities.